Correlation Between Microbial Diversity and Volatile Flavor Compounds of Suan zuo rou, a Fermented Meat Product From Guizhou, China - Wang, Hanyu; Su, Wei; Mu, Yingchun; Zhao, Chi (Frontiers in Microbiology, 2021)
Suan zuo rou (SZR), a traditional fermented meat from Guizhou province, China, is loved by local people for its unique flavor and nutritional value. However, the microbial communities and related flavor characteristics of SZR from different regions of Guizhou are unclear. We studied the correlation between the microbial communities and the physicochemical properties and volatile flavor compounds (VFCs) of 15 SZR samples from three regions in Guizhou province. The microbial community structure of SZR was determined by high-throughput sequencing and VFCs were identified by headspace-solid phase microextraction combined with gas chromatography-mass spectrometry. The results indicated that the microbial communities of SZR varied among the regions, as evidenced by the relative abundance of Weissella, Staphylococcus, Brochothrix, Kazachstania, and Debaryomces. There were also significant differences in pH, water activity, NaCl, and total volatile basic nitrogen (P < 0.05). Based on orthogonal projections to latent structures and Pearson’s correlation coefficient, we showed that Wickerhamomyces, Kazachstania, Lactobacillus, Weissella, Brochothrix, Debaryomyces, Staphylococcus, Pediococcus, Pichia, Candida, and Leuconostoc were highly correlated with 48 VFCs (| ρ| > 0.8, P < 0.05). Redundancy analysis showed that most of the dominant bacteria were positively related to water activity, whereas Lactobacillus was positively related with pH, and negatively related with total volatile basic nitrogen.